Pacific Languages An Introduction - Lynch, John (University of Hawai'i Press, 2018)
Almost one-quarter of the world's languages are (or were) spoken in the Pacific, making it linguistically the most complex region in the world. Although numerous technical books on groups of Pacific or Australian languages have been published, and descriptions of individual languages are available, until now there has been no single book that attempts a wide regional coverage for a general audience. Pacific Languages introduces readers to the grammatical features of Oceanic, Papuan, and Australian languages as well as to the semantic structures of these languages. For readers without a formal linguistic background, a brief introduction to descriptive linguistics is provided.In addition to describing the structure of Pacific languages, this volume places them in their historical and geographical context, discusses the linguistic evidence for the settlement of the Pacific, and speculates on the reason for the region's many languages.